TANGGUNG JAWAB NOTARIS ATAS AKTA YANG DIBATALKAN OLEH HAKIM (Studi Putusan Pengadilan Negeri Surakarta Nomor 151/Pdt.G/2010/Pn/Ska) - Rizki Putra Wicaksana (JURNAL ILMIAH NUSANTARA, 2025)
Notaries play a vital role in society, particularly in the drafting of authentic deeds, which constitute legal acts required by statutory regulations. A Notarial deed, as a strong means of evidence, may become null and void (batal demi hukum) if it contains errors or negligence, whether material or formal. The purpose of this study is to analyze the civil liability of Notaries for authentic deeds annulled by the court and to examine their legal consequences. This research employs a normative legal method using both the Conceptual Approach and the Statute Approach. The findings of the study are: first, Notaries may be held liable for both material and immaterial damages, as emphasized in the Decision of the Surakarta District Court No. 151/Pdt.G/2010/PN.Ska, which affirms that Notaries remain responsible even when the plaintiff does not claim material damages; and second, a defective Notarial deed may be downgraded to a private deed (akta di bawah tangan) or declared null and void, as affirmed in the same decision, where the court declared a deed of sale and purchase agreement and a power of attorney legalized by the Notary to be null and void.